2022
DOI: 10.1111/acfi.12966
|View full text |Cite
|
Sign up to set email alerts
|

Comments of the AFAANZ auditing and assurance standards committee on proposed international standard on auditing ISA for LCE

Abstract: | 4221 3. We believe that the authority may lead to confusion as to the applicability of the standard in that it will likely contribute to a disconnect between what is perceived to be a less complex entity and entities scoped into the standard. We recommend that the IAASB consider placing less emphasis on global prohibitions and place more emphasis on qualitative characteristics and jurisdictional discretion. (Question 3b) 4. We do not believe that the authority itself informs audit report users of the scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Inviting relevant interest groups to write comment letters is an important way to enable voices to be heard on accounting standards that can have a large impact (Hansen, 2011). It has been suggested that the ISA for LCEs can have a significant impact because the contribution of small- and medium-sized entities to local, regional, national and global economies, and society more broadly, cannot be underestimated (Coram et al. , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Inviting relevant interest groups to write comment letters is an important way to enable voices to be heard on accounting standards that can have a large impact (Hansen, 2011). It has been suggested that the ISA for LCEs can have a significant impact because the contribution of small- and medium-sized entities to local, regional, national and global economies, and society more broadly, cannot be underestimated (Coram et al. , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Inviting relevant interest groups to write comment letters is an important way to enable voices to be heard on accounting standards that can have a large impact (Hansen, 2011). It has been suggested that the ISA for LCEs can have a significant impact because the contribution of small-and medium-sized entities to local, regional, national and global economies, and society more broadly, cannot be underestimated (Coram et al, 2022). Larson and Herz (2013) suggested that asking for comment letters from interest groups promotes excellence, neutrality, the identification of unintended consequences and, ultimately, broad acceptance of the legitimacy of the standard that is suggested.…”
Section: Results Of the Textual Tone Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, a very limited number of studies have examined the ISA for LCEs. Coram et al (2022) provided a technical note that contained comments from the Auditing and Assurance Standards Committee of the Accounting and Finance Association of Australia and New Zealand (AFAANZ) concerning the proposed ISA for LCEs. To summarize, their study revealed that a stand-alone standard has the potential to contribute to achieving the goal of improving confidence in LCEs' financial reports, and they clearly supported the IAASB's continuance with this project.…”
Section: Introductionmentioning
confidence: 99%